Pendampingan dan Evaluasi Produk Kaki Prostetik bagi Kelainan Kongenital Kaki di Atas Lutut (Above Knee Prosthesis) - Menik Dwi Kurniatie GUNAWAN; Dita Ayu Mayasari; Dedi Nurcipto; Wisnu Adi Prasetyanto (Universitas Islam Indonesia, 2024)
A prosthetic leg is a lower extremity movement aid in assisting the mobility of persons with physical disabilities. A prosthetic leg is used to replace a missing leg, either due to a birth defect or an amputation. The use of a prosthetic leg is a different matter if the user has never experienced movement sensation. This service will evaluate the process of assisting the use of prosthetic legs for people with physical disabilities from birth. So far, prosthetic foot manufacturing services that have been carried out by the Prosthetic Orthosis Profession in Indonesia have focused on making sockets. Most users have physical abnormalities for a history of amputation or not birth defects. So that in the process of practicing the use of prosthetic legs there are no difficulties. It's different if the user of this prosthetic leg is congenital who has not felt the sensation of stepping movement at all or what is known as the gait cycle. Forms of community service activities in the process of assisting the use of prosthetic legs and evaluating any obstacles encountered in the walking process.